THE PORTRAIT OF THE ROMANIAN L2 USER AS A YOUNG [ROMANIAN!] MAN - Nicoleta NEȘU (Studia Universitatis Babeş-Bolyai. Philologia)
The Portrait of the Romanian L2 User as a Young (Romanian!) Man. The present study represents an attempt to sketch the portrait of a speaker of Romanian as a foreign language - a speaker, however, not at all ordinary, who does not fit into the categories already attested in the literature and who contains, in itself, a linguistic paradox: it refers to a less common, but increasingly numerous, category of young emigrant students of Romanian origin, native speakers of Romanian as an ethnic/heritage language, who have completed their entire pre-university school system in another country and in a language other than Romania/Romanian, and whom we meet as students enrolled in the specialization "Romanian language and literature" at universities abroad, therefore, by default, as a foreign language. Their profile is quite heterogeneous, even within the group, which makes it extremely interesting and challenging for who teaches. The process of creating a schematic, typical portrait of such a learner/speaker requires a necessarily interdisciplinary approach (linguistics, sociolinguistics, psycholinguistics), and its completion in terms of teaching strategies and methodology is still an open chapter, still being drafted and constantly updated. I should mention that all the data and information on which our analysis will be based are drawn from the experience of teaching Romanian abroad, within the Romanian language lectureship at the Sapienza University of Rome, Italy, and from our own research on this subject carried out in recent years.